Proceedings of the 16th ACM Great Lakes Symposium on VLSI 2006
DOI: 10.1145/1127908.1127946
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic instruction schedulers in a 3-dimensional integration technology

Abstract: We present the design of high-performance and energy-efficient dynamic instruction schedulers in a 3-Dimensional integration technology. Based on a previous observation that the critical path latency of a conventional dynamic scheduler is greatly affected by wire delay, we propose 3D-integrated scheduler designs by partitioning a conventional scheduler across multiple vertically-stacked die. The die-stacked organization reduces the lengths of critical wires thus reducing both latency and energy. Our simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 27 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…A number of design approaches are possible and many have been proposed, from alternating cores and memory/cache [20,23], to folding a single pipeline across layers [27].…”
Section: Baseline Architecturementioning
confidence: 99%
“…A number of design approaches are possible and many have been proposed, from alternating cores and memory/cache [20,23], to folding a single pipeline across layers [27].…”
Section: Baseline Architecturementioning
confidence: 99%
“…Paul Reed et al [8] has studied the 3D integrated memory-processor and analyzed the sense amplifier. In [9], the author has studied a 3D stacked register file with cache in high-performance microprocessor architecture. However, most of these works simply consider the 3D memory and the processor to be different level or only stack entire memory with another memory to increase cache capacity, at the same time, there are few works focusing on overall performance of the 3D processor.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive amount of research has demonstrated the latency reduction through additional device layers [1,2,3,4,30], however most prior art on 3D [4,5,6] is restricted to stacking traditional 2D dies. Such stacking offers significant reduction in inter-block latency, whereas it does little to help intra-block wire latency.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have provided block models for various architectural structures including 3D cache [9,12,13,14], register file [10,11] and instruction scheduler [30], along with 2D based placement tools such as [22]. However, these models are limited to folding blocks by wordlines or bitlines, and they do not explore further improvement from techniques such as port partitioning, which we shall discuss in Section 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation